Responses to potential captivity-induced stressors in captive-born cheetah (Acinonyx jubatus) : implications for behavioural and physiological stress and gastrointestinal health - Tordiffe, Adrian Stephen Wolferstan (University of Pretoria, 2023)
Thesis (PhD (Veterinary Science))--University of Pretoria, 2023.